Automatic oxygen titration with O2matic® to patients admitted with COVID-19 and hypoxemic respiratory failure. Issue 1 (1st January 2020) - Hansen, Ejvind Frausing; Bech, Charlotte Sandau; Vestbo, Jørgen; Andersen, Ove; Kofod, Linette Marie
ABSTRACT: Introduction: Patients with coronavirus disease (COVID-19) and pneumonitis often have hypoxemic respiratory failure and a need of supplementary oxygen. Guidelines recommend controlled oxygen, for most patients with a recommended interval of SpO2 between 92 and 96%. We aimed to determine if closed-loop control of oxygen was feasible in patients with COVID-19 and could maintain SpO2 in the specified interval. Methods: Patients were prospectively enrolled in an observational study on a medical ward dedicated to patients with COVID-19. Closed-loop controlled oxygen was delivered by O2matic® which can deliver 0–15 liters/min and adjusts flow every second based on 15 seconds averaging of SpO2 measured by pulse oximetry. Lung function parameters were measured at admission. Results: Fifteen patients (six women, nine men) participated in the study. Average age was 72 years. Lung function was severely impaired with FEV1, FVC and PEF reduced to approximately 50%. The average stay on the ward was 3.2 days and O2matic was used on average for 66 hours, providing 987 hours of observation. O2matic maintained SpO2 in the desired interval for 82.9% of the time. Time with SpO2 > 2% below interval was 5.1% and time with SpO2 > 2% above interval was 0.6%. Conclusion: Closed-loop control of oxygen to patients with COVID-19 is feasible and can maintain SpO2 in the specified interval in the majority of time. Closed-loop automated control could be of particular benefit for patients in isolation with decreased visibility, surveillance and monitoring. Further studies must examine the clinical benefits.